The caricatured image of Wilhelm II in Polish satirical press between 1888–1914 European context - Rydz, Romuald (Laughter, humour, satire, 2024)
The second half of the 19th century was a period of rapid development of the satirical press in Europe, which quickly became an important tool for shaping public opinion. With the development of printing technology, one of the main forms of influence of this type of publication became satirical drawings – caricatures. Thanks to the use of humor in such works, publishers of satirical periodicals could reach a much wider audience with their messages than before. The popularity of satirical press was also influenced by the topics that were addressed by caricature artists. Although they initially focused mainly on social issues, over time political issues became important for them. In particular, the caricaturists began portraying those involved in the struggle for power. For this reason, monarchs were a common subject of their interest. Among the European monarchs, the German Emperor Wilhelm II was of particular interest to satirists from the beginning of his reign. Due to his character traits, style of governance, and imperial ambitions, he became the subject of numerous caricatures printed in Europe and North America. Polish satirical publications also devoted a lot of attention to him. Many of them published caricatures of Wilhelm that were inspired by his actions on the international stage. However, what distinguished Polish caricaturists from their European counterparts was their use of themes related to the German policy towards the Polish community in the Prussian partition. As a result, the caricatures of Wilhelm and the satirical publications dedicated to him contributed to the consolidation of his image as a person responsible for the Germanization policies and the problems of Poles at the beginning of the 20th century.